2017
DOI: 10.1002/pca.2668
|View full text |Cite
|
Sign up to set email alerts
|

1H qNMR Quantification of Annonaceous Acetogenins in Crude Extracts of Annona muricata L. Fruit Pulp

Abstract: A simple, accurate and specific method for quantification of AAGs content was developed and validated for routine application to fruit pulp crude extracts. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…As a multi-disciplinary approach, the present study focused on designating phytochemicals from leaf extracts of soursop (Annona muricata), a plant known for its broad spectrum anti-cancer activity against osteosarcoma or bone cancer through analytical and in silico chemistry approach with con rmation from in vitro cell line studies. Annona muricata L, widely known as graviola or soursop is considered to have potential phytochemicals like phenols, saponins, terpenoids, avonoids, isoquinoline alkaloids and annonaceous acetogenins (Alali et al 1999;Bonneau et al 2017;Shanmugam et al 2022) that are reported to be effective against various cancer cell lines (Pieme et al 2014). Several research works have con rmed that the entire soursop tree exhibits selective and signi cant anticancer activity, with leaves being the most potent (Mishra et al 2013;Rupprecht et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…As a multi-disciplinary approach, the present study focused on designating phytochemicals from leaf extracts of soursop (Annona muricata), a plant known for its broad spectrum anti-cancer activity against osteosarcoma or bone cancer through analytical and in silico chemistry approach with con rmation from in vitro cell line studies. Annona muricata L, widely known as graviola or soursop is considered to have potential phytochemicals like phenols, saponins, terpenoids, avonoids, isoquinoline alkaloids and annonaceous acetogenins (Alali et al 1999;Bonneau et al 2017;Shanmugam et al 2022) that are reported to be effective against various cancer cell lines (Pieme et al 2014). Several research works have con rmed that the entire soursop tree exhibits selective and signi cant anticancer activity, with leaves being the most potent (Mishra et al 2013;Rupprecht et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Annonaceous acetogenins are present at a millimolar level in tropical plants from Annona genus. , Their various biological properties, both detrimental and beneficial, along with their widespread consumption, particularly as fruits, make their characterization an urgent need . The accurate structural characterization of acetogenins is difficult because of their long carbon chains.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize some of these problems, Nuclear Magnetic Resonance (NMR) spectrometry can be a suitable solution. NMR is a powerful technique for structure determination, that has also emerged as an important analytical tool in the biomedical and pharmaceutical field for quantitative determination of drugs in different matrices, providing high specificity and sensitivity [5][6][7]. Quantitative NMR (qNMR) have several advantages such as great reproducibility, automation, quantification without identical standard material, and total detection permitting an unbiased overview of the sample composition [8,9].…”
Section: Introductionmentioning
confidence: 99%